An oncolytic system produces oxygen selectively in pancreatic tumor cells to alleviate hypoxia and improve immune activation - Yu Chen; Jialun Wang; Ying Huang; Jianzhuang Wu; Yue Wang; Aotian Chen; Qiyuan Guo; Yixuan Zhang; Shu Zhang; Lei Wang; Xiaoping Zou; Xihan Li (Elsevier, 2024)
Introduction: Hypoxia is one of the important reasons for the poor therapeutic efficacy of current pancreatic cancer treatment, and the dense stroma of pancreatic cancer restricts the diffusion of oxygen within the tumor. Methods: A responsive oxygen-self-supplying adv-miRT-CAT-KR (adv-MCK) cascade reaction system to improve hypoxia in pancreatic cancer is constructed. We utilized various experiments at multiple levels (cells, organoids, in vivo) to investigate its effect on pancreatic cancer and analyzed the role of immune microenvironment changes in it through high-throughput sequencing. Results: The adv-MCK system is an oncolytic adenovirus system expressing three special components of genes. The microRNA (miRNA) targets (miRTs) enable adv-MCK to selectively replicate in pancreatic cancer cells. Catalase catalyzes the overexpressed hydrogen peroxide in pancreatic cancer cells to generate endogenous oxygen, which is catalyzed by killerRed to generate singlet oxygen (1O2) and further to enhance the oncolytic effect. Meanwhile, the adv-MCK system can specifically improve hypoxia in pancreatic cancer, exert antitumor effects in combination with photodynamic therapy, and activate antitumor immunity, especially by increasing the level of γδ T cells in the tumor microenvironment. Conclusion: The responsive oxygen-self-supplying adv-MCK cascade reaction system combined with photodynamic therapy can improve the hypoxic microenvironment of pancreatic cancer and enhance antitumor immunity, which provides a promising alternative treatment strategy for pancreatic cancer.